Entrepreneur and risk: a systematic literature review with a focus on small business - Fasone, Vincenzo; Puglisi, Mariano (Piccola Impresa / Small Business, 2019)
The term entrepreneur was introduced by Richard Cantillon (1755), by identifyingthe category of entrepreneurs as “the only one characterized by an actual risk,that is, by the fact or condition of buying at a certain price and selling to anuncertain price” (Blaug, 2000).The purpose of this study, as well as the main objective, is the analysis of theentrepreneur's attitude towards the risk. In particular, we will try to answer thefollowing questions: How is the behavior of the entrepreneur studied in situationsof risk? How is the behavior of the entrepreneur in situations of risk, in thecontext of SMEs?From the methodological point of view, it was decided to carry out a systematicreview of literature, with a narrative and critical chronological approach (Booth et al., 2012). A deductive approach was used in order to define a theoreticalframework on the subject that is being studied (Saunders et al., 2016) and amilestone for future research, also taking into account any empirical aspects.